Characterization of Patients with Poor Risk for Clinical Outcomes in Adult Symptomatic Lumbar Deformity Surgery. Issue 12 (15th June 2021) - Yagi, Mitsuru; Michikawa, Takehiro; Suzuki, Satoshi; Okada, Eijiro; Nori, Satoshi; Tsuji, Osahiko; Nagoshi, Narihito; Asazuma, Takashi; Hosogane, Naobumi; Fujita, Nobuyuki; Nakamura, Masaya; Matsumoto, Morio; et al.
Abstract : Study Design: Retrospective review of 159 surgically treated consecutive adult symptomatic lumbar deformity (ASLD) (65 ± 9 years, female: 94%) from a multicenter database. Objective: The aim of this study was to provide a comprehensive analysis of the risk of a poor clinical outcome in ASLD surgery. Summary of Background Data: Poor-risk patients with ASLD remain poorly characterized. Methods: ASLD was defined as age >40 years with a lumbar curve ≥30° or C7SVA ≥5 cm and Scoliosis Research Society 22 (SRS22) pain or function <4. Poor outcome was defined as 2y SRS22 total <4 or pain, function or satisfaction ⩽3. The outcomes of interest included age, sex, body mass index, bone mineral density, Schwab-SRS type, frailty, history of arthroplasty, upper-instrumented vertebral, lower-instrumented vertebral, levels involved, pedicle subtraction osteotomy, lumbar interbody fusion, sagittal alignment, global alignment and proportion (GAP) score, baseline SRS22r score, estimated blood loss, time of surgery, and severe adverse event (SAE). Poisson regression analyses were performed to identify the independent risks for poor clinical outcome. A patient was considered at poor risk if the number of risks was >4. Results: All SRS22 domains were significantly improved after surgery. In total, 21% (n = 34) reported satisfaction ⩽3 and 29% (n = 46) reported pain or function ⩽3. Poisson regression analysis revealed that frailty (odds ratio [OR]: 0.2 [0.1–0.8], P = .03), baseline mental-health (OR: 0.6 [0.4–0.9], P = .01) and function (OR: 1.9 [1.0–3.6], P < .01), GAP score (OR: 4.6 [1.1–18.7], P = .03), and SAE (OR: 3.0 [1.7–5.2], P < .01) were identified as independent risk for poor clinical outcome. Only 17% (n = 6) of the poor-risk patients reached SRS22 total score >4.0 at 2 years. Conclusion: The overall clinical outcome was favorable for ASLD surgery. Poor-risk patients continue to have inferior outcomes, and alternative treatment strategies are needed to help improve outcomes in this patient population. Recognition and optimization of modifiable risk factors, such as physical function and mental health, and reduced SAEs may improve overall clinical outcomes of ASLD surgery. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textRetrospective review of 159 surgically treated adult symptomatic lumbar deformity (ASLD) from a multicenter database was performed. The poor-risk patients continue to have dismal outcomes and warrant alternative treatment strategies to help improve outcomes. Recognition and optimization of modifiable risk factor may improve the overall clinical outcomes in ASLD surgery.